Structural Characterization of Laser Bonded Sapphire Wafers Using a Titanium Absorber Thin Film. Issue 5 (May 2015) - de Pablos-Martín, A.; Tismer, S.; Höche, Th.
Abstract : Two sapphire substrates were tightly bonded by irradiation with a 1064 nm nanosecond laser and using a sputtered 50 nm-titanium thin film as an absorbing medium. Upon laser irradiation, aluminum from the upper substrate is incorporated into the thin film, forming Ti–Al–O compounds. While the irradiated region becomes transparent, the bond quality was evaluated by scanning acoustic microscopy.